Comparison of horizontal and vertical dynamic visual acuity in patients with vestibular dysfunction and nonvestibular dizziness. - Roberts RA; Gans RE (Journal of the American Academy of Audiology, 2007)
Blurred vision with head movement is a common symptom reported by patients with vestibular dysfunction affecting the vestibulo-ocular reflex (VOR). Impaired VOR can be measured by comparing visual acuity in which there is no head movement to visual acuity obtained with head movement. A previous study demonstrated that dynamic visual acuity (DVA) testing using vertical head movement revealed deficits in impaired VOR. There is evidence that horizontal head movement is more sensitive to impaired VOR. The objective of this investigation was to compare horizontal and vertical DVA in participants with normal vestibular function (NVF), impaired vestibular function (IVF), and participants with nonvestibular dizziness (NVD). Participants performed the visual acuity task in a baseline condition with no movement and also in two dynamic conditions, horizontal head movement and vertical head movement. Horizontal DVA was twice as sensitive to impaired VOR than vertical DVA. Results suggest that horizontal volitional head movement should be incorporated into tasks measuring functional deficits of impaired VOR.